Synthesis of 3-Acetyl-1-Aryl-4,5-Dihydro-5,5-Dimethyl-1H-Trizoles from the Reaction of Nitrilimines with Acetone Oxime - EL-Rahman , Abed; S. Ferwanah, S. (Asian Journal of Chemistry, 2010)
A novel series of 3-acetyl-1-aryl-4,5-dihydro-5,5-dimethyl-1H-trizoles (7a–c) have been prepared via direct interaction between acetone oxime (3) and the appropriate hydrozonoyl chlorides (1) in presence of triethlamine.